Selection Of Coal Terminal Port Spare Parts Suppliers Using The AHP-Topsis Method - Rizky Ramadhani; Suparno Suparno (Journal Research of Social Science, Economics, and Management, 2025)
In the coal mining industry, the conveyor system is a vital component in ensuring the smooth distribution of coal from the stockpile to barges at the terminal port. PT X, one of the leading coal mining companies in Indonesia, faces challenges regarding the sustainability of conveyor operations, particularly in spare part procurement. Dependence on specific suppliers without continuous evaluation can pose risks such as delivery delays, price fluctuations, and operational downtime, which affect the company’s productivity. This study aims to develop a supplier selection model for spare parts at the Coal Terminal Port of PT X using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. AHP is employed to determine the priority weights of criteria based on expert assessments through pairwise comparisons, while TOPSIS is used to rank suppliers based on their relative closeness to the ideal solution. The AHP results indicate that the highest weighted criteria are Quality (35,59%), Services (29.59%), Delivery (15,93%), Cost (12,98%), and Profile (5,91%), while the top sub-criteria are Specification (19,30%), Certification (16,28%), followed by After-Sales Service (15,63%) and Warranty (13,97%) with a consistency ratio < 0,1. Supplier S1 ranks the highest with a preference value of 0,8837. Furthermore, to ensure the robustness of the TOPSIS ranking results, a sensitivity analysis was conducted by increasing or decreasing weights by 1%, and the top-ranked supplier remained unchanged. Thus, the TOPSIS method in this study is proven to be robust.